2018
DOI: 10.1088/1361-6528/aad756
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature synthesis of HfO2/HfO x heterostructures by ion-implantation

Abstract: Implantation of Hf films with oxygen ions is shown to be an effective means of fabricating high-quality HfO/HfO heterostructures at room temperature, with the layer composition and thicknesses determined by the ion energy and fluence. Implantation with 3 keV O ions to a fluence of 1 × 10 ions cm produces a polycrystalline (monoclinic-) HfO layer extending from the surface to a depth of ∼12 nm, and an underlying graded HfO layer extending an additional ∼7 nm, while implantation with 6 keV O to a similar fluence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The process of implantation in resistive switching devices has been introduced for various purposes. Some metal oxides, such as CuO x and HfO x , were synthesized at low temperature by implanting oxygen 21,22 . Metal or gas ions, such as oxygen, nitrogen, Au, Zr, and Ti, were also implanted in an effort to improve the resistive memory parameters, including the retention time, device yield, variations and forming voltage [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…The process of implantation in resistive switching devices has been introduced for various purposes. Some metal oxides, such as CuO x and HfO x , were synthesized at low temperature by implanting oxygen 21,22 . Metal or gas ions, such as oxygen, nitrogen, Au, Zr, and Ti, were also implanted in an effort to improve the resistive memory parameters, including the retention time, device yield, variations and forming voltage [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…Compositional changes caused by interface reactions and interdiffusion is one of the pivotal aspects in the operation of nonvolatile resistive switching devices. This process refers to the intricate interplay between the electrode and the metal oxide (e.g., HfO 2 , TaO 2 , and TiO 2 ), encompassing various redox processes and ionic migrations within the material. Understanding and controlling these effects is critical for optimizing the performance, stability, and reliability of memristive devices. , Further, recent studies have shown that the specific nature of volatile resistive switching in oxide-based devices depends strongly on the choice of electrodes and their reaction with the functional oxide layer. , For example, threshold switching is observed in Nb 2 O 5 -based devices that employ a reactive electrode (e.g., Nb, Ti, Cr, and TiN), while low-endurance, bipolar resistive switching is observed in devices with inert (e.g., Pt) electrodes . It has also been shown that resistive switching characteristics depend on the structure of the oxide film, with polycrystalline films requiring lower electroforming voltages than amorphous films due to grain-boundary conduction. , Since devices can be subjected to elevated temperatures during processing and/or operation (e.g., electroforming), it is important to understand how metal/oxide interactions and crystallization depend on the temperature .…”
Section: Introductionmentioning
confidence: 99%
“…The monoclinic phase is stable from RT up to 2000 K. The tetragonal phase is observed at 2000 K-2900 K. The highest symmetry cubic phase is stabilized between 2900 K and 3100 K. [13] The orthorhombic phase is typically not a stable phase under normal pressure conditions [14]. Various synthesis methods have been explored to optimize the physicochemical properties of HfO 2 and tailor its application-specific attributes [15][16][17][18]. Synthesizing hafnium oxide through various techniques allows for control over the particle size, morphology, and crystallinity of the hafnia, which in turn affects its properties and therefore is crucial for intentional tailoring of the material properties.…”
Section: Introductionmentioning
confidence: 99%